Konsistensi Mutu Dan Rendemen CPO (Crude Palm Oil) Di PT. Ciptamas Bumi Selaras Kabupaten Kaur Provinsi Bengkulu - Greastwonnio, Rifaldo; Widawati, Lina; Prasetya, Andwini (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 12 No 1 (2024): Maret, 2024)
The processed product known as crude palm oil is made by pressing and boiling the palm fruit. This study aims to determine the consistency of quality and yield at PT. Ciptamas Bumi Selaras, Kaur Regency, Bengkulu Province.  Data from daily reports on CPO  (Free Fatty Acids, water content, and impurity content)  quality were the study's resources  and CPO yield. In this study, the control chart was created using the Excel application as the data analysis tool. Then prepare cause-and-effect diagrams to find or analyze the causes of the emergence of these irregularities. The results showed that the quality of CPO (Free Fatty Acids, moisture content, and impurities) and yield produced by PT. Ciptamas Bumi Selaras from March 2022 to February 2023 were considered inconsistent. The Free Fatty acid and water content exceeded the upper limit (Upper Control Limit) in January 2023. The impurity content exceeded the upper limit in June 2022. Meanwhile, the yield was below the threshold (Lower Control Limit) in April and June 2022. Factors causing low-quality Free Fatty acid levels and yield are influenced by raw materials and processing. Meanwhile, the water content and impurities are influenced by raw materials, processing processes, and factory machine (equipment) conditions, as well as environmental hygiene conditions Keywords  :  quality consistency, crude palm oil ,  yield     Crude palm oil  (CPO) atau dikenal sebagai minyak sawit mentah adalah produk olahan hasil perebusan dan pengepresan daging buah kelapa sawit. Tujuan penelitian ini menganalisis konsistensi mutu dan rendemen di PT. Ciptamas Bumi Selaras Kabupaten Kaur Provinsi Bengkulu. Penelitian ini diperlukan data informasi harian mutu CPO (asam lemak bebas, kadar air, kadar kotoran) serta rendemen CPO. Metode analisis data pada penelitian ini membuat control chart menggunakan aplikasi excel. Sebab-sebab timbulnya masalah penyimpangan kualitas dan rendemen CPO dianalisis dengan cara penyusunan diagram sebab-akibat. Hasil penelitian memperlihatkan bahwa Mutu CPO (asam lemak bebas, kadar air dan kadar kotoran) dan rendemen yang dihasilan  PT. Ciptamas Bumi Selaras bulan Maret 2022 hingga Februari 2023 dinilai tidak konsisten. Kadar asam lemak bebas dan kadar air melewati batas atas ( Upper Control Limit ) terjadi pada Bulan Januari 2023. Kadar kotoran melewati batas atas pada Bulan Juni 2022. Rendemen berada di bawah ambang batas ( Lower Control Limit ) pada Bulan April dan Juni 2022. Bahan baku, proses pengolahan, kondisi mesin pabrik, dan kebersihan lingkungan memengaruhi kadar air dan kotoran. Kadar asam lemak bebas dan rendemen juga memengaruhi mutu.. Kata kunci :  konsistensi mutu, minyak sawit mentah, rendemen